(untitled) (Environment & Health, 2022)
Objective: The aim of the study was to assess the level of professional burnout among teachers of educational institutions of various types in the long-term dynamics, taking into account the forms of work organization. Materials and methods: During 2008 - 2021 the level of occupational burnout was monitored in 852 pedagogical workers of the Sumy region. The study was carried out according to the method of V. V. Boyko «Diagnostics of the level of occupational burnout». The study included three stages. In 2008, 420 teachers of secondary education institutions were surveyed. In 2020, 342 teachers of preschool and primary schools were examined. In 2021, 85 teachers of secondary education institutions were examined. In 2021, the organization of the educational process was taken into account. It included an online format in the context of the COVID-19 pandemic caused by the SARS-CoV-2 coronavirus, taking into account a history of coronavirus disease. Results: During the entire observation period, a low level of occupational burnout prevailed among teaching staff. Over the years, there has been a steady trend in the spread of the average level of occupational burnout, which has a negative sign of a protracted course with regular symptoms. The dependence of the development of the general syndrome of occupational burnout on age was established (r=-0,87, p